Beginning Reading and Academic Performance of Grade Two Pupils - Batogon, Trisha (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the beginning reading performance and academic achievement of Grade Two pupils in selected public elementary schools in Baras District, Division of Rizal during School Year 2025–2026. Specifically, it aimed to determine the pupils’ level of reading readiness, describe their socio-demographic profile, and identify the relationship between reading performance and academic performance. A descriptive research design was employed, utilizing documentary analysis and data from the Comprehensive Rapid Literacy Assessment (CRLA) and pupils’ first quarter grades. The respondents consisted of 301 Grade Two pupils selected through Slovin’s formula and simple random sampling.Findings revealed that most of the pupils were seven years old, female, first-born, and came from small families with one to two children. The majority of their parents were high school graduates, with fathers engaged in manual labor and mothers often unemployed, and belonging to a monthly income range of ₱10,000–₱14,999. In terms of reading performance, most pupils were classified under the High Emerging and Developing levels, indicating that they had not yet achieved the expected reading proficiency for their grade level, with only a few demonstrating fluency and comprehension skills. The academic performance of the pupils was rated as Fairly Satisfactory with a mean of 79.8. Statistical analysis showed no significant differences in reading performance in terms of age, sex, sibling position, number of children in the family, and father’s educational attainment. However, significant differences were found in relation to mother’s educational attainment, parents’ occupation, and monthly family income. Furthermore, a significant relationship was found between beginning reading performance and academic achievement.The study concluded that socio-economic factors, particularly maternal education, occupation, and family income, play a crucial role in pupils’ reading development and academic success. It recommends the implementation of reading intervention programs, parental involvement initiatives, and targeted instructional strategies to improve literacy outcomes among Grade Two Pupils.